Diagnostic performance of nucleic acid tests in tuberculous pleurisy - Han, Min (BMC Infect Dis, 2020)
BACKGROUND: Tuberculous pleurisy (TBP) is the most common form of extrapulmonary tuberculosis (TB). However, rapid diagnostic methods with high accuracy for tuberculous pleurisy are urgently needed. In the present study, we evaluated the diagnostic accuracy of Xpert MTB/RIF, LAMP and SAT-TB assay with pleural fluids from culture-positive TBP patients. METHODS: We prospectively enrolled 300 patients with exudative pleural effusions used as the samples for Xpert MTB/RIF, LAMP and SAT-TB assay. Of these, 265 including 223 patients diagnosed with TBP and 42 non-TBP patients used as controls were analyzed. RESULTS: The sensitivities of Xpert MTB/RIF (27.4%), LAMP (26.5%) and SAT-TB assay (32.3%) were significantly higher than that of pleural effusion smear (14.3%, X(2) = 20.65, P <  0.001), whereas they were much lower than expected for the analysis of pleural effusion samples. Both SAT-TB assay and Xpert MTB/RIF demonstrated high specificities (100%) and PPVs (100%), but the NPVs of all of the tests were < 22%. The area under ROC curve of pleural effusion smear, LAMP, Xpert MTB/RIF and SAT-TB assays was 0.524 (95% CI 0.431–0.617), 0.632 (95% CI 0.553–0.71), 0.637 (95% CI 0.56–0.714) and 0.673 (95% CI 0.6–0.745). SAT-TB assays had the highest AUC. CONCLUSION: Nucleic acid amplification tests are not the first choice in the diagnosis of tuberculous pleurisy. In this type of test, SAT-TB is recommended because of its low cost, relatively more accurate compared with the other two tests. This prospective study was approved by The Ethics Committee of the Shanghai Pulmonary Hospital (approval number: K19–148). TRIAL REGISTRATION: ClinicalTrials.gov identifier: ChiCTR1900026234 (Retrospectively registered). The registration date is September 28, 2019.